DATA ENVELOPE ANALYSIS OF IMPLEMENTATION OF ENERGY EFFICIENCY MEASURES IN THE VEGETABLE OIL INDUSTRY - Kuchkarova, D.T.; Shermatov, B.A. (Educational Research in Universal Sciences, 2023)
Fat is oil in the industry applied electricity of proceedings models using energy thrifty processes apply and them analysis to do opportunity there is. Fat is oil industry to develop new himself control to do technologies apply through is achieved. This is his in turn, energy thrifty of methods used without good quality product work release requirement is enough It is known that oil is oil in the industry applied machine tools electricity in transmitters electricity of energy big part consumption does, therefore for them energy savings modes control to do and control to do important.